Molecular dynamics study of tribological properties of AlCoCrFeNi high entropy alloy coatings on Al substrate - Xianhe Zhang; Zhenrong Yang; Hongyun Wang; Cun Zhang; Xiaofei Wang (Advances in Mechanical Engineering, 2025)
High entropy alloys exhibit superior mechanical properties, especially wear resistance, making them crucial for wear-resistant and surface protection applications, necessitating in-depth research into their wear resistance and coating materials. This study utilizes molecular dynamics methods to perform a comprehensive investigation and meticulous analysis of the wear resistance of FeNiCrCoAl high entropy alloys, with the goal of providing crucial theoretical support for their practical applications. The FeNiCrCoAl high entropy alloy was applied as a coating onto an Al substrate, serving as the subject of friction simulations. By regulating the indentation depth of abrasive particles and coating thickness, we systematically examined how these factors affect the friction properties of the material. The findings reveal that when the depth of abrasive pressing is less than the coating thickness, the friction coefficient rises with increasing pressing depth; conversely, when the pressing depth exceeds the coating thickness, the friction coefficient decreases. As the coating thickness increases, the material generates a reduced proportion of disordered lattice structures during friction, accompanied by an increase in dislocation line density. This suggests a reduced wear from abrasive particles, indicating that thicker coatings enhance the material’s wear resistance.